Timing and style of high-temperature metamorphism across the Western Gawler Craton during the Paleo- to Mesoproterozoic. Issue 8 (17th November 2019) - Reid, A. J.; Halpin, J. A.; Dutch, R. A.
Abstract: Combined in situ monazite dating, mineral equilibria modelling and zircon U–Pb detrital zircon analysis provide insight into the pressure–temperature–time ( P – T – t ) evolution of the western Gawler Craton. In the Nawa Domain, pelitic and quartzo-feldspathic gneisses were deposited after ca 1760 Ma and record high-grade metamorphic conditions of ∼7.5 kbar and 850 °C at ca 1730 Ma. Post-peak microstructures, including partial plagioclase coronae and late biotite around garnet, and subtle retrograde garnet compositional zoning, suggest that these rocks cooled along a shallow down-pressure trajectory across an elevated dry solidus. In the northwest Fowler Domain (Colona Block), monazite grains from pelitic gneisses record two stages of growth/recrystallisation interpreted to represent discrete parts of the P–T path: (1) ca 1710 Ma monazite growth during prograde to peak conditions, and (2) ca 1690 Ma Y-enriched monazite growth/recrystallisation during partial garnet breakdown and cooling towards the solidus. Relict prograde growth zoning in garnet suggests rocks underwent a steep up- P path to peak conditions of ∼8 kbar at 800 °C. The new P–T–t results suggest basement rocks of the southwestern Nawa and northwestern Fowler were buried to depths of 20–25 km during the Kimban Orogeny, ca 10 Myrs after the sedimentary precursors were deposited. The P–T path for the Kimban Orogeny is broadly anti-clockwise, suggesting that at least the early phase of this event was associated with extension. Exhumation of rocks from both the southwestern Nawa and northwestern Fowler domains may have occurred during the waning stages of the Kimban Orogeny (< ca 1690 Ma). The limited low-grade overprint in these rocks may be explained by a mid-to-upper crustal position for these rocks during the subsequent Kararan Orogeny. Aluminous quartz-feldspathic gneiss of the Nundroo Block in the eastern Fowler Domain records peak conditions of ∼7 kbar at 800 °C. Monazite grains from the Nundroo Block are dominated by an age peak at ca 1590 Ma, although the presence of some older ages up to ca 1690 Ma, possibly reflect partial resetting of older monazite domains. The P – T – t conditions suggest these rocks were buried to 20–25 km at ca 1590 Ma during the Kararan Orogeny. This high-grade metamorphism in the Nundroo Block is a mid-crustal expression of the same thermal anomaly that caused magmatism in the central-eastern Gawler Craton. Juxtaposition of rocks affected by the Kimban and Kararan orogenic events in the western Gawler Craton was controlled by lithospheric-scale shear zones, some of which have facilitated ∼20 kilometres of exhumation.